Rustler's moon eaudiobook Ransom canyon series, book 2. - Thomas, Jodi (Ransom Canyon, 2016)
On a dirt road marked by haunting secrets, three strangers caught at life's crossroads must decide what to sacrifice to protect their own agendas.and what they're each willing to risk for love. If there's any place that can convince Angela Harold to stop running, it's Ransom Canyon. And if there's any man who can reveal desires more deeply hidden than her every fear, it's Wilkes Wagner. Beneath the rancher's honorable exterior is something that just might keep her safe.or unwittingly put her in danger's path. With his dreams of leaving this small Texas town swallowed up by hard, dusty reality, all Wilkes has to show for his life is the Devil's Fork Ranch. Though not one to let false hope seduce him, he can't deny the quiet and cautious beauty who slips into his world and changes everything. Lauren Brigman finally has freedom at her fingertips. All she needs is Lucas Reyes's attention-a look, a touch, some sign that she's more to him than a girl he rescued one dangerous night. But now it's her turn to rescue someone, and the life-altering decision may cost her more than a chance with Lucas.